Endo‐α‐Mannosidase‐Catalyzed Transglycosylation. (29th May 2017) - Iwamoto, Shogo; Kasahara, Yuta; Yoshimura, Yayoi; Seko, Akira; Takeda, Yoichi; Ito, Yukishige; Totani, Kiichiro; Matsuo, Ichiro
Abstract: In order for facilitating the synthesis of oligosaccharides, transglycosylation reactions mediated by glycoside hydrolases have been studied in various contexts. In this study, we examined the transglycosylating activity of a Golgi endo ‐ α‐mannosidase. We prepared various glycosyl donors and acceptors, and recombinant human Golgi endo ‐α‐mannosidase and its various mutants were expressed. The enzyme was able to mediate transglycosylation from α‐glycosyl‐fluorides. Systematic screening of various point mutants revealed that the E407D mutant had excellent transglycosylation activity and extremely low hydrolytic activity. Substrate specificity analysis revealed that minimum motif required for glycosyl acceptor is Manα1– 2Man. The synthetic utility of the enzyme was demonstrated by generation of a high‐mannose‐type undecasaccharide (Glc1 Man9 GlcNAc2 ). Abstract : Golgi endo ‐α‐mannosidase (G‐EM) as a trans ‐glycosylation catalyst : Transglycosylation mediated by glycoside hydrolases is valuable for the chemo‐enzymatic synthesis of oligosaccharides. We developed a novel transglycosylation reaction mediated by a mutant of G‐EM (E407D) with α‐fluorinated glucosyl mannoside as a donor. This reaction was applied to the synthesis of a natural high‐mannose‐type dodecasaccharide.